Implementasi Media Pop Up Book Pada Materi Tata Surya Terhadap Pemahaman Peserta Didik - Nurfadhilah, Alifah Aulia; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the implementation of the use of pop-up book learning media in solar system material in elementary schools. The pop up itself has a three-dimensional component that provides a distinctive, attractive and meaningful appearance and can change when the page is opened so that it can attract students' attention. The success of a teacher in the teaching and learning process can be seen from the implementation of learning objectives, one of which is that students can understand and master the material presented by the teacher. This research is descriptive qualitative in nature using a literature study approach. Data collection through searching for sources and compiling data from various sources such as books, journals and existing research. The data obtained from various reference sources is described critically and must be in-depth so that it can support the propositions and ideas. Based on the results of the analysis by researchers from several sources above, it can be concluded that the implementation of pop up book media can help students in elementary schools understand the solar system learning material.